The Protagonist Characterization In Monster University Movie’s Script - Pahotan Sinaga; Elita Modesta Br Sembiring; Karana Jaya Tarigan; Faido Marudut Pardamean Simanjuntak (Universitas PGRI Semarang, 2023)
This research entitled The Protagonist Characterization in Monster University Movie. The problems in this study are (1) How are the Protagonist Characters portrayed in Monster University Movie and (2) How are the protagonist's struggles depicted in the Movie. This research is relevant to descriptive qualitative method to analyze the characterization and the struggle of the characters. The source of the data is the Monster University movie’s script. By applying the theory of Boggs (2008) this study aims to depend protagonist character and how the character’s struggle in Monster University movie. By doing the data analysis, it is found that the protagonist character namely Mike that has good personality while Sulley is reckless, arrogant, angry, and always giving up the monster. However, they become one and then they are very good and scarer monster ever. In their struggle, Mike and Sulley faced their struggle with the physical of themselves. It teaches people how to behave in life by having good character. Thus, this study contributes to enrich the reference of literature study for it is essential in teaching people in life.